POTENSI JAMUR ENDOFIT ASAL CABAI SEBAGAI AGENS HAYATI UNTUK MENGENDALIKAN LAYU FUSARIUM (Fusarium oxysporum) PADA CABAI DAN INTERAKSINYA - Sri Endah Nurzannah; Lisnawita Lisnawita; Darma Bakti (Jurnal Agroekoteknologi, 2014)
This research aims to find endophytic fungi which potency as biocontrol agents to against Fusariumoxysporum on chili and their interaction. The research was conducted at Plant Disease Laboratory,Agroecotechnology Program Study, Faculty of Agriculture, University of Sumatera Utara andgreenhouse of plant quarantine, Medan from May to August 2013. It was done by using CompletelyRandomized Design (CRD) Non Factorial with fourteen treatments and three replications. Theresults showed all the endophytic fungi used (Rhizopus sp., Penicillium sp., Rhizoctonia sp.,Aspergillus sp., Hormiscium sp., Geotrichum sp.) potential as biological agents to control fusariumwilt on chilli. The best results obtained on Penicillium sp. with disease severity was 2.78% in thegreenhouse test . Penicillium sp. also able to improve plant growth with plant height 29.40 cm.Key words : chilli, Fusarium oxysporum, endophytic fungi, interaction